Using a Subject Pronoun in Object Position to Claim Power - Pasch, Helma; Mbolifouye, François (AAeO - Afrikanistik-Aegyptologie-Online, 2011)
The verb fu ’give’ in Zande usually governs a direct object of INANIMATE gender and optionally a recipient of HUMAN gender. Only when the transfer of a person of low social status to a new environment by a person of higher social status is described, the direct object (and patient) is of HUMAN gender. In case this person is referred to pronominally, this is done by a pronoun of series 2, which indicates –CONTROL, while the pronouns of series 1 indicate +CONTROL. In one of the Zande stories published by Evans-Pritchard, the verb fu ’give’ has the pronoun mi ’I’ of series 1 as a direct object. In the given context, this is in agreement with the feature +CONTROL of mi, but not entirely with its syntactic role. The different reactions by speakers of Zande, some of which rejected the construction as not grammatical while others accepted it as the only appropriate way of describing the given asymmetrical situation of power, reflect this apparent mismatch.